Monetary privacy in the information economy: bank confidentiality in Monaco - Donaghy, Matthew (2002)
Offshore financial centres (OFCs), such as Switzerland and the Cayman Islands, increasingly have to exchange information on their financial activities, reflecting broader trends in what Castells has termed the `information economy'. However, what kind of information is being exchanged within and across offshore jurisdictions and what does this mean for the confidentiality of client information, so long the hallmark of `offshore' operations? On the basis of some recent research undertaken in the OFC of Monaco, this article argues that while information exchange represents an important dynamic within the contemporary international financial system, a culture of privacy remains a constitutive feature in the way that these centres operate. The author shows that Monaco is working hard to develop, not undermine, such a culture through structural, institutional, dispositional and spatial changes. Such an argument questions some prevailing theoretical discourses which view modern economies as being essentially information driven. - Reproduced.
Keywords: Monetary policy; Banks